Quantitative assessment of steel reinforcement effects on gamma-ray shielding in reinforced concrete using Monte Carlo simulations - Sanchit Saxena; Suman Kumar; Hrishikesh Sharma; Poonam Kumari (Case Studies in Construction Materials)
Reinforced concrete (RC) is ubiquitous in critical infrastructure, yet the role of steel reinforcement volume and configuration in radiation shielding remains poorly understood. This study demonstrates that rebar configuration is just as influential as steel volume in determining gamma-ray shielding effectiveness. Through 576 Monte Carlo simulations across the 500–8000 keV gamma energy spectrum, we demonstrated that variations in reinforcement geometry at fixed steel percentages can alter linear attenuation coefficients (LAC) by up to 29 %, with optimized configurations enhancing shielding performance by 19 % over analytical predictions. Remarkably, spatial optimization enables RC sections to achieve attenuation equivalent to structures containing 81 % more steel volume, redefining material efficiency in radiation shielding. An SD factor is reintroduced, enabling precise LAC predictions of RC sections with near-perfect accuracy (R² > 0.98) across energies. This metric allows engineers to reduce steel use while maintaining shielding—e.g., 8 mm rebars at 60 mm spacing match 10 mm rebars at 70 mm spacing (26 % reduction). By bridging particle physics and structural engineering, this work provides a framework for designing RC structures in nuclear facilities, medical bunkers, and radioactive waste storage. The findings redefine shielding design standards, emphasizing that rebar configuration is as critical as steel volume for safe, sustainable, and cost-effective radiation protection.